Pengaruh Beban Kerja Dan Program Pelatihan Berbasis Digital Terhadap Kepuasan Kerja Dengan Kualitas Pelayanan Sebagai Variabel Interveling Pada ” PT Pasoka Sumber Karya Jl Raya Indarung Padang” - Rangga Eka Putra; Vicky Brama Kumbara; Andre Ilyas (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of workload and digital-based training programs on job satisfaction, with service quality as an intervening variable, at PT Pasoka Sumber Karya. This study used a quantitative approach with a survey method. The population and sample size for this study consisted of 65 respondents, determined using a total sampling technique. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of the SmartPLS application. There is a negative and significant influence of Workload on Service Quality, There is a positive and insignificant influence of Digital-Based Training Programs on Service Quality, There is a negative and significant influence of Workload on Job Satisfaction, There is a negative and insignificant influence of Digital-Based Training Programs on Job Satisfaction, There is a positive and insignificant influence of Service Quality on Job Satisfaction, There is a negative and insignificant influence of Workload on Job Satisfaction Through Service Quality, There is a positive and insignificant influence of Digital-Based Training Programs on Job Satisfaction Through Service Quality, The contribution of Workload and Digital-Based Training Program variables to Job Satisfaction is 0.910 or 91.0%, while the remaining 9.0% is influenced by other variables not examined in this study, The contribution of Workload and Digital-Based Training Program variables to Service Quality is 0.817 or 81.7%, while the remaining 18.3% is influenced by other variables not examined in this study.